Psycossocial necessities of the client at the unit of chest pain: issues for caring in the emergency room - Andrade, Karla Biancha (Online Brazilian Journal of Nursing, 2004)
This study represents the account of clients under diagnostic investigation in the Chest Pain Unit who expect the positive or negative validation for their diagnosis of heart disease. The study aims to identify the account of clients admitted to the Chest Pain Unit who are expecting to have their diagnosis of heart disease defined, as well as the necessities they may present during such period. Communication was used as a means to achieve results. It is a qualitative survey whose approach was the method of social representations. The periodo of data construction was between July and October 2002. A semi-structured interview plan was used and six clients under diagnostic investigation in the Chest Pain Unit answered it. Based on the analyzed answers, distress corresponded to the core representation, with anxiety/anguish and fragility as significant elements, wherefrom arose the needs of care towards attitudes of care, spirituality and comfort. This study reveals the importance to use communication as a basic instrument and as interpersonal process on the nurse/client relationship.